Rethinking Oncologic Facial Nerve Reconstruction in the Acute Phase Through Classification of the Level of Injury - Winter, Jessica M.; Dimovska, Eleonora O.F.; Tzou, Chieh-Han John; Rodriguez-Lorenzo, Andres (Facial Plastic Surgery, 2024)
Early facial nerve reconstruction should be offered in every patient with oncological resections of the facial nerve due to the debilitating functional and psychosocial consequences of facial nerve palsy. Oncologic pathology or oncologic resection accounts for the second most common cause of facial nerve palsy. In the case of these acute injuries, selecting an adequate method for reconstruction to optimize functional and psychosocial well-being is paramount. Authors advocate consideration of the level of injury as a framework for approaching the viable options of reconstruction systematically. Authors breakdown oncologic injuries to the facial nerve in three levels in relation to their nerve reconstruction methods and strategies: Level I (intracranial to intratemporal), Level II (intratemporal to extratemporal and intraparotid), and Level III (extratemporal and extraparotid). Clinical features, common clinical scenarios, donor nerves available, recipient nerve, and reconstruction priorities will be present at each level. Additionally, examples of clinical cases will be shared to illustrate the utility of framing acute facial nerve injuries within injury levels. Selecting donor nerves is critical in successful facial nerve reconstruction in oncological patients. Usually, a combination of facial and nonfacial donor nerves (hybrid) is necessary to achieve maximal reinnervation of the mimetic muscles. Our proposed classification of three levels of facial nerve injuries provides a selection guide, which prioritizes methods for function nerve reconstruction in relation of the injury level in oncologic patients while prioritizing functional outcomes.
Keywords: facial nerve classification; facial paralysis injury; nerve; reconstruction; surgical oncology